Unmodified Titanium Dioxide Nanoparticles as a potential contrast agent in photon emission computed tomography - Khalid, A.; Ahmad, P.; Alharthi, A. I.; Muhammad, S.; Khandaker, Mayeen Uddin *; Faruque, M. R. I.; Din, I. U.; Alotaibi, M. A. (MDPI, 2021)
Highly crystalline titanium dioxide nanoparticles (TiO2 -NPs) are synthesized via a simple hydrothermal technique. After structural and compositional analysis, the as-synthesized unmodified TiO2 -NPs are tested for improvement in two modes of kilovoltage radiation therapy and singlephoton emission computed tomography (SPECT)/computed tomography (CT). Our results show that the unmodified TiO2 -NPs provide an observable enhancement in CT scan image contrast ranging from 0 ± 3 HU (without NPs) to 283.7 ± 3 HU (0.23 g/mL). TiO2 -NPs has excellent biocompatibility, selective uptake at target sites, and reduced toxicity. The unmodified TiO2 -NPs as a contrast agent can significantly improve the existing methods of diagnosing and treating cancer.